Descriptive Analysis on the Structure of Mendriq Verb Phrase: (Analisis Deskriptif terhadap Struktur Frasa Kerja Bahasa Mendriq) (Jurnal Bahasa, 2014)
This paper elucidates the type of verbs that are available in the Mendriq language. The data for this research data are primary data collected from native speakers of Mendriq. Mendriq is a language spoken by the Mendriq indigenous people at Kuala Lah, Gua Musang, Kelantan. This is a moribund language spoken by only 245 people in three villages: Kampung Kuala Lah, Kampung Baru and Kampung Kuala Stail. This study is based on six months of fieldwork conducted at Kuala Lah. The data were collected from ten native speakers of Mendriq language through a story-telling method. The conversations were recorded using a digital recorder. Later, the data were translated by a translator who was appointed by the Department of Aborigines in Kelantan. The data comprises various types of sentences. However, this study focuses on the verb phrases of the Mendriq language only. The analysis performed on the data is a descriptive analysis. The analysis shows that the verb phrases of Mendriq include transitive and intransitive verbs. Both types of verbs can also be followed by auxiliary verbs: modals and aspects. Therefore, this descriptive analysis is able to explain the two types of verbs and two types of auxiliary verbs in Mendriq. The findings could be the platform for a theoretical analysis in the near future.Keywords: transitive verbs, intransitive verbs, Mendriq, moribund language, auxiliary verbs